Digital Capabilities and Circular Economy Practices to Enhance Environmental and Economic Performance: The Role of Digital Technology-Environmental Strategy Alignment - Turkcan, Hulya; Imamoglu, Salih Zeki; Ince, Huseyin; Erat, Serhat (Wiley, 2025)
Although digitalization and circularity are two major topics today, studies on their relations and also their effects on firm outcomes are still scarce. In this regard, revealing the impact of digital capabilities on circular economy practices and how they relate to firm performance advances related literature. Moreover, there is no study in the literature on how to strengthen the relationship between digital capabilities and circular economy practices. Accordingly, this research investigates the relationship between digital capabilities and circular economy practices with the moderating effect of digital technology-environmental business strategy alignment. Furthermore, their impacts on environmental and economic performance are examined. Based on survey data from 204 manufacturing firms, this research reveals that digital capabilities relate to circular economy practices, and digital technology-environmental business strategy alignment strengthens this relationship. It is further demonstrated that digital capabilities indirectly affect environmental and economic performance through the mediating role of circular economy practices. This research, therefore, opens a new avenue for future exploration and contributes to the literature by providing a novel and in-depth explanation of the relationship between digital capabilities and circular economy practices, demonstrating the strengthening role of digital technology-environmental business strategy alignment, and revealing their effects on economic and environmental performance within the context of a developing country. Moreover, this research offers a new and thorough perspective for practitioners on how digital capabilities provide greater value for circular economy practices and their importance for economic and environmental performance.
Keywords: circular economy practices; digital capabilities; digital technology-environmental strategy alignment; economic performance; environmental performance